From inner to dyadic connection: the role of mindfulness in mother–infant interaction during the first year of life - Passaquindici, Ilenia; Pastore, Massimiliano; Nardozza, Odette; Lionetti, Francesca; D’Urso, Giulio; Palumbo, Riccardo; Fasolo, Mirco; Spinelli, Maria (Frontiers in Behavioral Neuroscience, 2024)
Introduction: Mother-infant attunement is fundamental to support infant socio-emotional development. Based on the assumption that we connect better with others if we are aware of and connected with our own experience, mindfulness could affect maternal ability to attune to the infant. However, little is known about this topic in the first year of life. Study 1 aimed to investigate the role of maternal dispositional mindfulness and mindful parenting in mother-infant physiological and behavioral attunement at 3 months of age. Study 2 aimed to explore the effect of a mindfulness-based intervention not specific of parenting experience on mother-infant behavioral and physiological attunement and on maternal well-being at 9 months of age. Methods: In Study 1, mother-infant (n = 67) behavioral and physiological attunement (i.e., co-regulation and RSA) were collected simultaneously each 20 sec during face-to-face interaction. Mothers completed questionnaires about their dispositional mindfulness and mindful parenting. In Study 2, mother-infant dyads were randomly divided into a control (n = 20) and intervention group (n = 29). The intervention group attended a 5 weeks mindfulness-based intervention. At T1 and T2, the same procedure described in Study 1 was applied and mothers reported about their well-being. Results: Results showed that maternal mindfulness was associated with high physiological and behavioral attunement at 3 months, and with more positive maternal behaviors and less stress at 9 months. Analysis evidenced a slight improvement in the intervention group in maternal dispositional mindfulness and a reduction in parenting stress at T2. Discussion: Findings from both studies suggested that maternal mindfulness could represent a protective factor that could support mothers to foster better dyadic interactions with their infants. The implementation of mindfulness-based interventions for mothers could have preventive and clinical implications.